Smart grid home - Wells, Quentin (Australia : Cengage Learning, 2013)
Covers such topics as reducing home energy consumption by eliminating heat loss and heat transfer, reducing the power-on time of electronics and other power equipment without loss of convenience, automating home electrical systems to maximize energy conservation, and timing the use of electricity in the home to save both energy and money.
1. Introduction to the Smart Grid. 2. Smart Meters and in Home Displays. 3. Developing a Home Energy Efficiency Plan. 4. Developing a Home Energy Efficiency Plan- Part 2. 5. Upgrade Home Energy Efficiency by Reducing Heat Transfer. 6. Taming the Energy Hogs in your Home. 7. Energy Efficiency Lighting and Entertainment Systems. 8. Home Automation and Lighting Control. 9. Solar Power for Your Home. 10. Wind Turbine Power for your Home.
Includes index.
Keywords: Dwellings -- Electric equipment; Dwellings -- Energy consumption; Home automation